O patrimonialismo na administração pública : os cargos em comissão - Grison, Leonardo (Universidade do Vale do Rio dos Sinos, 2011)
The present's work theme is the relationship between the government and the bureaucratic stament, focusing on the "cargos em comissão". The stament means the group of people, which comes from the bureaucratic chart of the patrimonial state, which is managed as a family asset. This work reflects research conducted within the Post-Graduate Program in Law of UNISINOS, and as such, brings his influences, especially of interdisciplinarity. In this case, it establishes a dialogue with sociology, searching in Weber and Raymundo Faoro, the main but not exclusive, theoretical. The work is located in the line of research Hermeneutics, Constitution and Implementation of Rights, especially because the research is focused on the Brazilian State, with focus on its public machine. The method of procedure of this thesis is bibliographic, with input of statistical data to corroborate the literature. The method of approach is the hermeneutic-phenomenological. The study aims to show how the past patrimonialist, as demonstrated by Brazilian sociologist Raymundo Faoro, still persists, especially in cases such as in the charges in commission. Defined as of free appointment and dismissal by the Constitution, are used in order to gift fellow politicians, through appointments. Are analyzed the types of domination proposed by Weber and the historical formation of the patrimonialist state, its transition to Brazil, until the proclamation of the Constitution of 1988, verifying that the reality of patrimonialism remain, especially in regard to the "cargos em comissão", and its purpose of benefiting the bureaucratic chart
Keywords: Administração pública; Estamento; Patrimonialismo; Cargos em comissão; Public administration; Stament; Patrimonialism; ACCNPQ::Ciências Sociais Aplicadas::Direito